Tanggung Jawab Ayah Terhadap Nafkah Anak Setelah Perceraian dalam Tinjauan Hukum Islam dan Undang-undang Nomor 35 Tahun 2014 tentang Perlindungan Anak (Studi Kasus di Kelurahan Cengkeh Turi Kecamatan Binjai Utara) - Rizki Pratama; Azhar (Peduli Riset dan Pengabdian Masyarakat, 2024)
This study aims to determine the implementation of fulfilling child support after parental divorce in Cengkeh Turi Village, North Binjai District. The formulation of the problem proposed in this study is: What is the father's responsibility for providing for his child after a divorce occurs in Cengkeh Turi Village, North Binjai District. What legal measures can be taken by the mother (father) to carry out his responsibility in providing support for his child after this occurs divorce in Cengkeh Turi Village, North Binjai District. What is the impact on fathers who do not provide for their children after divorce in Cengkeh Turi Village, North Binjai District in terms of Law Number 35 of 2014 concerning Child Protection and the Compilation of Islamic Law. This research is empirical legal research, with data collection through literature study and interviews with respondents who are the custodians of the child. To analyze the research results, a statutory regulation approach and a sociological approach are used based on what actually happens in people's lives. The results of this study show that the implementation of fulfilling child support after parental divorce in Klaten Regency has not been fully implemented well. This is caused by the family's economic factors and this factor is the cause of a large number of divorces. In fact, in terms of providing maintenance, it is the father's responsibility, even after a divorce, because this has been stated in the Court Decision and must be implemented; and if the Court Decision is not implemented, then efforts can be made in the form of submitting a request for implementation of the decision to the Religious Court and providing a warning letter to the party who does not implement it. This research provides suggestions, namely the need to disseminate information to the public regarding the efforts made to fulfill their rights in Court Decisions, because there are still many people who do not know this, and this results in their rights not being fulfilled.